Administration of Ketamine Causes Autophagy and Apoptosis in the Rat Fetal Hippocampus and in PC12 Cells - Li, Xinran; Li, Yanan; Zhao, Jinghua; Li, Lina; Wang, Yuxin; Zhang, Yiming; Li, Yue; Chen, Yu; Liu, Wenhan; Gao, Li (Frontiers in Cellular Neuroscience, 2018)
Drug abuse during pregnancy is a serious problem. Like alcohol, anticonvulsants, sedatives, and anesthetics, such as ketamine, can pass through the placental barrier and affect the growing fetus. However, the mechanism by which ketamine causes damage to fetal rats is not well understood. Therefore, in this study, we anesthetized pregnant rats with ketamine and evaluated the Total Antioxidant Capacity (T-AOC), Reactive Oxygen Species (ROS), and Malondialdehyde (MDA). Moreover, we determined changes in the levels of Cleaved-Caspase-3 (C-Caspase-3), Beclin-1, B-cell lymphoma-2 (Bcl-2), Bcl-2 Associated X Protein (Bax), Autophagy-related gene 4 (Atg4), Atg5, p62 (SQSTM1), and marker of autophagy Light Chain 3 (LC3). In addition, we cultured PC12 cells in vitro to determine the relationship between ROS, autophagy, and apoptosis following ketamine treatment. The results showed that ketamine induced changes in autophagy- and apoptosis-related proteins, reduced T-AOC, and generated excessive levels of ROS and MDA. In vitro experiments showed similar results, indicating that apoptosis levels can be inhibited by 3-MA. We also found that autophagy and apoptosis can be inhibited by N-acetyl-L-cysteine (Nac). Thus, anesthesia with ketamine in pregnant rats may increase the rate of autophagy and apoptosis in the fetal hippocampus and the mechanism may be through inhibition of antioxidant activity and ROS accumulation.